2020
DOI: 10.1002/adtp.201900214
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Potential Immunological Effects of Boiling Histotripsy for Cancer Treatment

Abstract: Boiling histotripsy (BH) is a completely non-invasiveultrasonic technique that can be used to mechanically destroy tumor tissues. Studies have shown that BH has biological effects on immune responses, but the mechanisms involved in the induction and enhancement of systemic anti-tumor immune responses after BH treatment are poorly understood. The present study therefore investigates the anti-tumor immune responses triggered by BH exposure in vivo. In a syngeneic tumor model, BH treatment results in more dendrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…These findings [13][14][15][16] suggest that HIFU mechanical ablation alone, without the need for adjuvants, is sufficient to enhance ICI therapy for the treatment of cancers that are unresponsive to ICIs. One advantage of HIFU mechanical ablation over HIFU thermal ablation is that tumor fragmentation instead of tumor coagulation may protect TAAs and DAMPs from protein denaturation by excessive heat and stimulate more effective antitumor immune responses [15,16,33,41].…”
Section: High-intensity Focused Ultrasound Mechanical Ablation-enhancmentioning
confidence: 90%
See 2 more Smart Citations
“…These findings [13][14][15][16] suggest that HIFU mechanical ablation alone, without the need for adjuvants, is sufficient to enhance ICI therapy for the treatment of cancers that are unresponsive to ICIs. One advantage of HIFU mechanical ablation over HIFU thermal ablation is that tumor fragmentation instead of tumor coagulation may protect TAAs and DAMPs from protein denaturation by excessive heat and stimulate more effective antitumor immune responses [15,16,33,41].…”
Section: High-intensity Focused Ultrasound Mechanical Ablation-enhancmentioning
confidence: 90%
“…Notably, the combination therapy improved long-term survival, achieved complete bilateral tumor regression, and induced an effective long-term immune memory response to suppress subsequent tumor engraftment. Other recent studies found that histotripsy stimulated more potent intratumoral CD8 T cells and antigen presentation than HIFU thermal ablation in a murine breast cancer model [15] and melanoma model [16]. One recent study showed that combining histotripsy with intratumor anti-CD40 agonist antibody, αCTLA-4, and anti-PD-L1 antibody (αPD-L1) significantly improved the therapeutic efficacy against ICI refractory murine melanoma [17].…”
Section: High-intensity Focused Ultrasound Mechanical Ablation-enhancmentioning
confidence: 99%
See 1 more Smart Citation
“…Boiling histotripsy of the tumor tissue via the application of ultrasounds is similar to the effects of IRE ( 248 ). The mechanism is similar and the methods seem complimentary and both modulate the immunophenotype of CD8+ cells to a phenotype which is more cytotoxic toward cancer cells.…”
Section: Physical Methods and Their Mechanismsmentioning
confidence: 99%
“…Histotripsy is a novel, non-thermal, image guided ablation modality using pulsing regimens to generate cavitation bubble clouds that lead to precise non-thermal tumor ablation that can rapidly kill cells in a targeted region with millimeter precision [60]. Several works established that there is an immune response to histotripsy ablation in many tumors, however a definite mechanism behind this response has not been established [61][62][63].…”
mentioning
confidence: 99%